2008
DOI: 10.1007/s00268-008-9549-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Depth of NIM EMG Endotracheal Tube for Intraoperative Neuromonitoring of the Recurrent Laryngeal Nerve During Thyroidectomy

Abstract: We concluded that the mean depth of the NIM EMG tube would be a useful reference value for detecting the malposition of electrodes and adjusting the depth of tube during the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 35 publications
2
109
1
2
Order By: Relevance
“…Surgeon should appreciate the vocal cords are located approximately 1/2 way down the thyroid cartilage. If maximum shunt stimulation occurs at the level of the cricothyroid membrane, anterior arch of the cricoid or lower, one assumes excessive endotracheal tube depth [6][7][8][9][10][11] (c) Repeat laryngoscopy to check correct tube positioning (d) Contralateral VN stimulation. If the contralateral vagus does not have a good EMG reading, a recording side (i.e.…”
Section: Operative Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…Surgeon should appreciate the vocal cords are located approximately 1/2 way down the thyroid cartilage. If maximum shunt stimulation occurs at the level of the cricothyroid membrane, anterior arch of the cricoid or lower, one assumes excessive endotracheal tube depth [6][7][8][9][10][11] (c) Repeat laryngoscopy to check correct tube positioning (d) Contralateral VN stimulation. If the contralateral vagus does not have a good EMG reading, a recording side (i.e.…”
Section: Operative Techniquementioning
confidence: 99%
“…We tested and analysed the RLN with stimulation electric current/intensity of 1 mA for definitive confirmation [12]. To optimise the RLN and VN response, we routinely dissected the nerves free from overlying soft tissue, in a strictly bloodless dry field [6][7][8][9][10][11]. The RLN was dissected meticulously to the entry of the larynx.…”
Section: Rln Identification and Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lu et al studied optimal depth of the NIM EMG tube for RLN monitoring. They found that 5.7% of the tubes required tube depth adjustment, even when placing the tube so that the electrodes were in contact with the vocal cords during direct laryngoscopy [7].…”
Section: Case #3mentioning
confidence: 99%
“…The electromyography (EMG) monitoring system represented by Nerve Integrity Monitor (NIM) (Medtronic Xomed, Jacksonville, FL, USA) is useful for RLN and SLNEB preservation in cases in which the tumor is large, or if there is tumor invasion into the adjacent tissue. Recently, RLN monitoring with an EMG has become widely applied (1)(2)(3)(4)(5)(6)(7)(8)(9). Intraoperative nerve monitoring is necessary for nerve function preservation.…”
Section: Introductionmentioning
confidence: 99%